Reduction of Mitophagy-Related Oxidative Stress and Preservation of Mitochondria Function Using Melatonin Therapy in an HT22 Hippocampal Neuronal Cell Model of Glutamate-Induced Excitotoxicity - Wang, Dan-dan; Jin, Mei-fang; Zhao, Dong-jing; Ni, Hong (Frontiers in Endocrinology, 2019)
Recent evidence indicates that autophagy-mediated mitochondrial homeostasis is crucial for oxidative stress-related brain damage and repair. The highest concentration of melatonin is in the mitochondria of cells, and melatonin exhibits well-known antioxidant properties. We investigated the impact and mechanism involved in mitochondrial function and the mitochondrial oxidative stress/autophagy regulator parameters of glutamate cytotoxicity in mouse HT22 hippocampal neurons. We tested the hypothesis that melatonin confers neuroprotective effects via protecting against mitochondrial impairment and mitophagy. Cells were divided into four groups: the control group, melatonin alone group, glutamate injury group and melatonin pretreatment group. We found that glutamate induced significant changes in mitochondrial function/oxidative stress-related parameters. Leptin administration preserved mitochondrial function, and this effect was associated with increased superoxide dismutase, glutathione (GSH), and mitochondrial membrane potential and decreased GSSG (oxidized glutathione) and mitochondrial reactive oxygen species. Melatonin significantly reduced the fluorescence intensity of mitophagy via the Beclin-1/Bcl-2 pathway, which involves Beclin-1 and Bcl-2 proteins. The mitophagy inhibitor CsA corrected these glutamate-induce changes, as measured by the fluorescence intensity of Mitophagy-Tracker Red CMXROS, mitochondrial ROS, and mitochondrial membrane potential changes. These findings indicate that melatonin exerts neuroprotective effects against glutamate-induced excitotoxicity by reducing mitophagy-related oxidative stress and maintaining mitochondrial function.